THE FIRST RECORD OF CAMBRIAN CONODONTS FROM THE HUQF-HAUSHI OUTCROPS, OMAN, ARABIAN PENINSULA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
Outcrops of Cambrian sediments of the uppermost Miqrat Formation, the Al Bashair Formation and the basal Barik Formation were sampled for conodont and palynomorph studies. The units are part of the Palaeozoic Haima Supergroup, exposed in the Huqf-Haushi area in central eastern Oman, Arabian Peninsula. Palynomorphs were absent but conodont samples yielded a small conodont fauna. The presence of Muellerodus? erectus allows the recognition of the Muellerodus? erectus Zone established for North China (late Paibian – early Jiangshanian), in accordance with previous reports on the trilobite fauna from the same interval.